A SMALL WORLD OPTIMIZATION FOR MULTIPLE OBJECTS OPTIMIZATION OF MIXED-MODEL ASSEMBLY LINE PROBLEM WITH PARALLEL MACHINE - Seker, Sukran; Ozgurler, Mesut (WORLD SCIENTIFIC PUBL CO PTE LTD, 2012)
Mixed Model Assembly Line (MMAL) are widely used in manufacturing industries, becauseMMAL fulfills the diversified demand from small-high product. This paper presents an integer programming model for the mixed model assembly line problem (MMALBP). The proposed mathematical model minimizes the cycle time and select assembly sequences. The proposed model includes parallel machines in some stations. Integer programming formulation is presented for balancing and scheduling decisions simultaneously for mixed model assembly line problem which have parallel machines in stations. The proposed approach is illustrated with a computational example problem.
Keywords: Computer Science